Materials and articles in contact with foodstuffs. Plastics substances subject to limitation. Guide to the test methods for the specific migration of substances from plastics into food and food simulants and the determination of substances in plastics and the selection of conditions of exposure to food simulants Part 1, (15th June 1999) - British Standards Institution
No abstract available